Study on indole alkaloidal components from the roots of tabernaemontana peduncularis wall. (Apocynaceae) - Paramate Chaitongruk (Prince of Songkla University, 2004)
Thesis (M. Pharm.,Pharmaceutical Sciences)--Prince of Songkla University, 2004